Targeting pyruvate kinase M2 contributes to radiosensitivity of non-small cell lung cancer cells in vitro and in vivo. Issue 2 (28th January 2015) - Meng, Mao-Bin; Wang, Huan-Huan; Guo, Wen-Hao; Wu, Zhi-Qiang; Zeng, Xian-Liang; Zaorsky, Nicholas G.; Shi, Hua-Shan; Qian, Dong; Niu, Zhi-Min; Jiang, Bo; Zhao, Lu-Jun; Yuan, Zhi-Yong; et al.
Highlights: PKM2 was elevated in almost five NSCLC cell lines examined compared to autologous normal lung bronchial epithelial cell. Knockdown of PKM2 expression enhanced IR-induced apoptosis and autophagy, accompanied by inhibiting AKT and PDK1 phosphorylation, but enhancing ERK and GSK3βphosphorylation in vitro and in vivo . Abstract: Aerobic glycolysis, a metabolic hallmark of cancer, is associated with radioresistance in non-small cell lung cancer (NSCLC). Pyruvate kinase M2 isoform (PKM2), a key regulator of glycolysis, is expressed exclusively in cancers. However, the impact of PKM2 silencing on the radiosensitivity of NSCLC has not been explored. Here, we show a plasmid of shRNA-PKM2 for expressing a short hairpin RNA targeting PKM2 (pshRNA-PKM2) and demonstrate that treatment with pshRNA-PKM2 effectively inhibits PKM2 expression in NSCLC cell lines and xenografts. Silencing of PKM2 expression enhanced ionizing radiation (IR)-induced apoptosis and autophagy in vitro and in vivo, accompanied by inhibiting AKT and PDK1 phosphorylation, but enhanced ERK and GSK3β phosphorylation. These results demonstrated that knockdown of PKM2 expression enhances the radiosensitivity of NSCLC cell lines and xenografts as well as may aid in the design of new therapies for the treatment of NSCLC.